HIF Stabilizer Desidustat Protects against Complement-Mediated Diseases - Patel, Vishal J.; Joharapurkar, Amit A.; Kshirsagar, Samadhan G.; Patel, Maulik S.; Savsani, Hardikkumar H.; Dodiya, Harshad S.; Rakhasiya, Milan H.; Patel, Ashvin K.; Sundar, Rajesh; Jain, Mukul R. (Drug Research, 2024)
Complement cascade is a defence mechanism useful for eliminating pathogenic microorganisms and damaged cells. However, activation of alternative complement system can also cause inflammation and promote kidney and retinal disease progression. Inflammation causes tissue hypoxia, which induces hypoxia-inducible factor (HIF) and HIF helps the body to adapt to inflammation. In this study, we investigated the effect of HIF stabilizer desidustat in complement-mediated diseases. Oral administration of desidustat (15 mg/kg) was effective to reduce the kidney injury in mice that was induced by either lipopolysaccharide (LPS), doxorubicin or bovine serum albumin (BSA)-overload. Complement activation-induced membrane attack complex (MAC) formation and factor B activity were also reduced by desidustat treatment. In addition, desidustat was effective against membranous nephropathy caused by cationic BSA and retinal degeneration induced by sodium iodate in mice. C3-deposition, proteinuria, malondialdehyde, and interleukin-1ß were decreased and superoxide dismutase was increased by desidustat treatment in cBSA-induced membranous nephropathy. Desidustat specifically inhibited alternative complement system, without affecting the lectin-, or classical complement pathway. This effect appears to be mediated by inhibition of factor B. These data demonstrate the potential therapeutic value of HIF stabilization by desidustat in treatment of complement-mediated diseases.
Keywords: complement system; prolyl hydroxylase inhibitor; glomerulonephritis